2007
DOI: 10.1111/j.1551-2916.2007.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of the Dissolution of Spherical Alumina Particles in CaO–Al2O3–SiO2 Melts

Abstract: The dissolution of alumina spheres in a synthetic CaO–Al2O3–SiO2 (CAS) slag was investigated in situ with a confocal scanning laser microscope (CSLM) in the temperature range between 1470° and 1630°C. Through image analysis, the evolution of the apparent particle radius is obtained as a function of time, exhibiting a clear temperature dependence. The rate‐limiting step of the dissolution process is first evaluated with respect to the classical shrinking core model. Neither the boundary layer diffusion nor the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 16 publications
0
84
0
Order By: Relevance
“…CSLM work has been carried out on the dissolution phenomena of MgO, Al 2 O 3 and MgAl 2 O 4 microparticles in the CaO-SiO 2 -Al 2 O 3 (-MgO) slags. [12][13][14][15][16] Consequently, in the present study, the dissolution of SiC particle at 1600 • C in the CaO-SiO 2 -MnO slag is observed in situ by means of CSLM and analyzed in order to make the determination of dissolution 0955-2219/$ -see front matter © 2010 Elsevier Ltd. All rights reserved. doi:10.1016/j.jeurceramsoc.2010.07.020 mechanism, which has not been clarified yet, more straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…CSLM work has been carried out on the dissolution phenomena of MgO, Al 2 O 3 and MgAl 2 O 4 microparticles in the CaO-SiO 2 -Al 2 O 3 (-MgO) slags. [12][13][14][15][16] Consequently, in the present study, the dissolution of SiC particle at 1600 • C in the CaO-SiO 2 -MnO slag is observed in situ by means of CSLM and analyzed in order to make the determination of dissolution 0955-2219/$ -see front matter © 2010 Elsevier Ltd. All rights reserved. doi:10.1016/j.jeurceramsoc.2010.07.020 mechanism, which has not been clarified yet, more straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…This result was similar to that of previous studies. [5,6,[20][21][22][23][24] Therefore, R d was calculated using Eq. [1]:…”
Section: A Diffusion Coefficient and Activation Energy For Sio 2 Dismentioning
confidence: 99%
“…In recent years, Monaghan and Chen [16], Fox and Valdez et al [17], Verhaeghe and Liu et al [18], Liu and Verhaeghe et al [19], and Orrling and Sridhar et al [20] employed laser scanning confocal microscopy (CSLM) to investigate the dissolution of inclusions in slag. CSLM enables the in -situ observation of the dissolution of inclusions.…”
Section: Methodsmentioning
confidence: 99%